Molecular basis of antibody‐mediated neutralization and protection against flavivirus. Issue 10 (7th September 2016) - Dai, Lianpan; Wang, Qihui; Qi, Jianxun; Shi, Yi; Yan, Jinghua; Gao, George F.
Abstract: Antibody‐mediated humoral immunity plays a pivotal role in flavivirus control. Neutralizing antibodies targeting viral envelope (E) protein, provide protection against flaviviruses in vivo but can also promote virus infection by antibody‐dependent enhancement when antibodies are weakly neutralizing or in subneutralizing concentrations. The molecular basis for antibody‐mediated virus neutralization can be revealed by structural studies of monoclonal antibodies complexed with the E protein or virion. In addition, the flavivirus non‐structural protein NS1 can also induce host antibody production, and some of these antibodies can provide protection against virus challenge. In this review, we summarize the known structures of flavivirus neutralizing or protective antibodies bound to their epitopes and describe the underlying molecular mechanisms. © 2016 IUBMB Life, 68(10):783–791, 2016